Envolvimento dos sistemas gabaérgicos e glutamatérgicos na atividade ansiolítica-símile do hidroxicitronelal - Andrade, Jéssica Cabral de (2022)
Hydroxycitronellal (HC) is a monoterpene obtained from the semisynthesis of citronellal and is widely used as a fragrance in cosmetics. Some monoterpenes have already been studied in relation to their activities on the central nervous system, including anxiolytic activity. The objective of this work was to evaluate the possible anxiolytic-like activity of HC, and its possible mechanism of action using in vivo and in silico methodologies. Male Swiss mice (Mus musculus) were treated with HC (12.5; 25 and 50 mg/kg, i.p.) and submitted to rota rod, elevated plus maze (LCE), open field (AC) and perforated plate (PP). The possible involvement of GABAA and NMDA receptors was verified using the blockers flumazenil and ketamine, respectively, in the ECL. No significant difference was observed in the rota rod test, in relation to the negative control group, for the motor activity of the animals treated with HC, indicating the absence of myorelaxant or sedative effect. In the elevated plus maze, HC (at the three doses) induced a significant increase in the percentage of entries (34.8%, 33.8%, and 38.6%, respectively) and length of stay (49.9%, 56.1% and 57.0%, respectively) in the open arms of the LCE, as well as increased the number of crossings in the open field model and the number of crossings and dips in the perforated plate, indicating an anxiolytic-like activity. The anxiolytic-like activity was reversed after the use of the GABAA receptor antagonist. The administration of the antagonist ketamine in association with HC resulted in an increase in the number of entries and time spent in the open arms of the LCE, even at sub-active doses. In silico studies showed a stable interaction between HC and amino acids present at GABAA receptors, suggesting that HC has a positive allosteric modulation on the GABAA (29.52; -5.38; 37,94 kcal/mol) receptor, and on NMDA (-52,30 kcal/mol) glutamate receptors. Pharmacokinetic data show that HC has satisfactory parameters, such as good bioavailability. These results suggest that the possible mechanism of action of the anxiolytic-like activity of the compound can be attributed, possibly, to the involvement of GABAergic and glutamatergic neurotransmission, which are essential in the functioning of the CNS. Thus, it is concluded that HC has anxiolytic-like activity, and may be a possible candidate for a future drug.